Pragmatism: Contemporary Educational Approach - critical study – - belguarmi, Siham (Journal of Social Sciences and Humanities, 2021)
Pragmatism is a method of reflection, where everything must be subjected to experimentation to prove the validity of the idea. Education has been impacted as a philosophy, field or practice by this intellectual tendency which seeks to improve and develop human capacities to contribute effectively to the construction and development of society. So pragmatism denies the existence of objective truths and absolute values and affirms that the truth is the discovery of the invention of something new, and not the discovery of the existing, and that its measurement is based on its utility in the world of work. Thus, the question that arises in this article is is: to what extent can pragmatism be used to guide education in the human interest? In other words, is it possible to rely entirely on this intellectual tendency to translate our educational programs and the decisions of our schools in order to keep abreast of the progress made in today's world? And what is the impact of this pragmatic philosophy on education and values for our children today? The research attempted to provide a critique of the philosophy of pragmatic education, especially those implicitly attached to values.